Penile‐preserving surgery for male distal urethral carcinoma followed by buccal mucosa urethroplasty. Issue 4 (27th May 2019) - Kitamura, Yosuke; Horiguchi, Akio; Ojima, Kenichiro; Kawamura, Kazuki; Shinchi, Masayuki; Asano, Tomohiko; Ito, Keichi; Azuma, Ryuichi
Abstract : Introduction: We report a case of distal urethral carcinoma treated with segmental urethral excision and reconstruction by staged buccal mucosa urethroplasty. Case presentation: A 60‐year‐old man presented with difficulty urinating and a palpable mass on the ventral side of his penis. He was diagnosed as having localized distal urethral carcinoma (cT2N0M0) and underwent penile‐preserving surgery with staged urethroplasty using buccal mucosa as substitute tissue. The pathological diagnosis was squamous cell carcinoma of the urethra (T2) with negative surgical margin. At 2 years of follow‐up, there was no recurrence or metastasis, he could void in a standing position with an acceptable urinary stream, and he found the appearance of his external genitalia acceptable. Conclusion: In cases of distal primary urethral carcinoma, urethroplasty using buccal mucosa graft could be alternative treatment option providing a better postoperative quality of life.